Turning wood into green bioproducts. Issue 6 (November 2019) - Unknown
Abstract : The process of using crude oil to produce petroleum can negatively affect the environment. One biotechnology research company has developed a biomass fractionation process using waste wood and low-cost ionic fluids to produce sustainable bioproducts for the industry.